Preparation method of a xylan / fullerene derivative composite material and its antioxidant and anti-inflammatory applications

Fullerene material was solved by esterifying betaine with fullerol and combining with xylan to prepare a xylan/fullerene derivative composite with high water solubility and strong antioxidant and anti-inflammatory ability. The problem of insufficient water solubility and targeting in biological applications has achieved effective antioxidant and anti-inflammatory effects in biological bodies.

CN117159727BActive Publication Date: 2025-01-03JIANGNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310989276.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-01-03
Estimated Expiration
2043-08-08

AI Technical Summary

Technical Problem

The existing fullerene materials have problems such as insufficient water solubility, low bioavailability and poor targeting in biological applications, resulting in limited antioxidant and anti-inflammatory effects.

Method used

Fullerene derivatives are prepared by esterification reaction of betaine with fullerol and combined with xylan to form xylan/fullerene derivative composite materials, which is enhanced by using the amphoteric carboxylate properties of betaine Fullerene anti-inflammatory and electrostatic self-assembly capabilities.

Benefits of technology

The water solubility, antioxidant and anti-inflammatory capabilities of fullerene composite materials have been improved, and nanoparticles with high-efficiency antioxidant and targeting effects have been formed, which are suitable for the antioxidant and anti-inflammatory fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117159727B_ABST
    Figure CN117159727B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a xylan / fullerene derivative composite material and its anti-oxidation and anti-inflammatory application, belonging to the technical field of nanomaterials. The method comprises: mixing betaine, DMAP and EDC in a certain proportion, activating for a certain period of time, adding a certain amount of fullerol, mixing and stirring to react, and dialyzing to remove EDC, DMAP and unreacted betaine and fullerol after the reaction. Centrifuging the dialyzed solution, taking the supernatant and freeze-drying to obtain a fullerene derivative. The obtained fullerene derivative is mixed with a certain amount of xylan in deionized water, stirred for reaction, dialyzed to remove unreacted reactants, and freeze-dried to obtain a xylan / fullerene derivative composite material. The xylan / fullerene derivative composite material obtained by the method of the invention is extremely hydrophilic, has excellent free radical scavenging performance and anti-inflammatory ability, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a xylan / fullerene derivative composite material and its anti-oxidation and anti-inflammatory applications, belonging to the technical field of nanomaterials. Background Art

[0002] Reactive oxygen species (ROS) are a class of active substances commonly found in organisms, which can maintain the redox balance in cells, thereby affecting cell growth or apoptosis. However, excessive ROS can cause oxidative damage, reduce the antioxidant capacity of cells, and even cause DNA, lipid and protein damage, affecting cell activity, and ultimately leading to inflammation, aging, neurodegenerative diseases, etc. Therefore, people hope to find antioxidant materials to absorb excess ROS to achieve the purpose of relieving inflammation.

[0003] Fullerene is an excellent antioxidant with high chemical stability and unique physical and chemical properties. The conjugated π bonds between the hexagonal and pentagonal structures on the surface of fullerene molecules determine that it can effectively capture free radicals and scavenge ROS, and has strong antioxidant and anti-inflammatory properties. However, intrinsic fullerenes have problems such as insufficient water solubility, low bioavailability, and poor targeting, which greatly limits their application in life sciences. Grafting hydrophilic functional groups on the surface of fullerene is a common choice to improve its water solubility. The connection between the introduced polar groups and fullerenes can greatly adjust the dipole moment and band gap, ultimately leading to better hydration thermodynamics and thus improving the water solubility of fullerene derivatives. Coating a layer of responsive hydrophilic substances on the surface of fullerene is another way to improve the bioavailability of fullerene. Unfortunately, fullerene complexes obtained by coating with traditional solubilizing substances such as surfactants often face the problem of active sites being covered and reduced antioxidant properties. Therefore, combining the two methods of solubilization and grafting functional groups to prepare a fullerene complex that has both water solubility, bioresponsiveness, and antioxidant and anti-inflammatory capabilities is an inevitable choice for the application of fullerenes in life fields such as medicine and cosmetics. Summary of the invention

[0004] In order to solve the above problems, the present invention first provides a method for preparing a xylan / fullerene derivative composite material, the method comprising:

[0005] (1) betaine, DMAP, and EDC are mixed and stirred in a certain proportion, activated for a period of time, and then a certain amount of fullerene alcohol is added, mixed and stirred to react, and after the reaction is completed, dialysis is performed to remove EDC, DMAP and unreacted betaine and fullerene alcohol; the dialyzed solution is centrifuged, and the supernatant is freeze-dried to obtain a fullerene derivative;

[0006] (2) The obtained fullerene derivative is mixed with a certain amount of xylan in deionized water, stirred for reaction, dialyzed to remove unreacted reactants, and freeze-dried to obtain a xylan / fullerene derivative composite material.

[0007] In one embodiment of the present invention, in step (1), the mass ratio of DMAP to EDC is 3:(3-7), wherein the optimal mass ratio of DMAP to EDC is 3:5.

[0008] In one embodiment of the present invention, in step (1), the mass ratio of fullerenol to betaine is 1:(1-10); more preferably 1:7-8.

[0009] In one embodiment of the present invention, in step (1), the dialysis days = 1-5 days, wherein the optimal dialysis days is 3 days.

[0010] In one embodiment of the present invention, in step (1), the mass ratio of EDC to betaine is 1:(2-5).

[0011] In one embodiment of the present invention, in step (1), the activation temperature is 10-35°C, wherein the optimal activation temperature is 25°C.

[0012] In one embodiment of the present invention, in step (1), the activation time is 0.5-2 h, wherein the optimal activation time is 1 h.

[0013] In one embodiment of the present invention, in step (1), the temperature of the mixed reaction is 10-90°C, wherein the optimal reaction temperature is 25°C.

[0014] In one embodiment of the present invention, in step (1), the mixing reaction time is 12-36 hours, wherein the optimal reaction time is 24 hours.

[0015] In one embodiment of the present invention, in step (2), the mass ratio of the fullerene derivative to xylan is 1:3-3:1, and more preferably 1:1.

[0016] In one embodiment of the present invention, in step (2), the dispersion concentration of the fullerene derivative in deionized water is 0.5-3 mg / mL; specifically, 1 mg / mL may be selected.

[0017] In one embodiment of the present invention, in step (2), the temperature of the mixed reaction is 10-50°C, wherein the optimal reaction temperature is 25°C.

[0018] In one embodiment of the present invention, in step (2), the mixing reaction time is 12-36 hours, wherein the optimal reaction time is 24 hours.

[0019] In one embodiment of the present invention, in step (2), the centrifugal conditions are a rotation speed of 5000-10000 r / min and a centrifugal time of 4-10 min, wherein the optimal centrifugal conditions are a rotation speed of 8000 r / min and a centrifugal time of 6 min.

[0020] In one embodiment of the present invention, during the activation process of preparing fullerene derivatives, the reaction solution is colorless and transparent, and after adding fullerol, the solution system is yellow-brown, and after the reaction is completed, the solution is yellow-brown.

[0021] In one embodiment of the present invention, during the preparation of the fullerene derivative, the upper layer of the solution after centrifugation is a clear yellow-brown solution with almost no precipitation.

[0022] In one embodiment of the present invention, the method specifically includes the following process:

[0023] Betaine, DMAP, and EDC are mixed and stirred in a certain proportion, activated for one hour, and then a certain amount of fullerol is added, mixed and stirred for reaction, and dialyzed after the reaction to remove EDC, DMAP, and unreacted betaine and fullerol. After dialysis for 3 days, the solution is centrifuged, and the supernatant is freeze-dried to obtain a fullerene derivative. The obtained fullerene derivative is mixed with a certain amount of xylan in deionized water, stirred for reaction, dialyzed to remove unreacted reactants, and freeze-dried to obtain a xylan / fullerene derivative composite material.

[0024] In one embodiment of the present invention, the yield of the fullerene derivative is 6.12%, and the mass ratio of xylan / fullerene derivative to fullerene derivative is 1.27.

[0025] The present invention provides a xylan / fullerene derivative composite material based on the above method.

[0026] The present invention also provides the use of the xylan / fullerene derivative composite material in the preparation of antioxidant and anti-inflammatory preparations.

[0027] In the present invention, xylan is negatively charged, and intrinsic fullerene or its common water-soluble fullerene derivative fullerol (prepared by introducing hydroxyl groups into fullerene) are not charged, which leads to weak electrostatic interaction force when the two are combined, and it is difficult to form a strong coating effect. Betaine is a kind of amphoteric carboxylate alkaloid, which has extremely low biological toxicity and has anti-tumor and anti-peptic ulcer properties. The fullerene derivative obtained by esterification of betaine and fullerol can carry a certain degree of positive charge, which can further enhance the anti-inflammatory ability of fullerene while effectively improving the electrostatic self-assembly ability between fullerene complex and xylan, forming a good encapsulation structure. The coating combination of xylan and fullerene derivatives is conducive to giving fullerene unique enzyme response characteristics, achieving targeted and synergistic anti-inflammatory effects.

[0028] Beneficial Effects of the Invention

[0029] The present invention provides a method for preparing a xylan / fullerene derivative composite material, that is, a fullerene composite material with extremely high water solubility is prepared through a few simple steps. The prepared xylan / fullerene derivative composite material has a small particle size, strong water solubility, high antioxidant and anti-inflammatory ability, low cytotoxicity, and can be well applied in the field of antioxidant and anti-inflammatory. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the infrared spectrum (FT-IR) spectrum of fullerenol.

[0031] Figure 2 is the H NMR spectrum of fullerene alcohol ( 1 H NMR) spectrum.

[0032] Figure 3 This is the thermogravimetric (TGA) diagram of fullerene.

[0033] Figure 4 This is the infrared spectrum (FT-IR) spectrum of fullerene derivatives.

[0034] Figure 5 is the H NMR spectrum of fullerene derivatives ( 1 H NMR) spectrum.

[0035] Figure 6 The diagram shows the preparation principle and structural formula of fullerene derivatives.

[0036] Figure 7 This is the infrared spectrum (FT-IR) of xylan / fullerene derivatives.

[0037] Figure 8 This is a scanning electron microscope (SEM) image of xylan / fullerene derivatives.

[0038] Fig. 9 This is the dynamic light scattering (DLS) diagram of xylan / fullerene composite material.

[0039] Fig.10 Antioxidant activity of xylan / fullerene derivative composites: NO inhibition assay.

[0040] Fig.11 Antioxidant activity of xylan / fullerene derivative composites: Superoxide radical inhibition assay.

[0041] Fig.12 Figure 2 shows the cytotoxicity of xylan / fullerene derivative composites.

[0042] Fig.13 This is the fluorescence intensity diagram of xylan / fullerene derivative composite material under laser confocal microscope.

[0043] Fig.14 Dynamic light scattering (DLS) graphs of composite materials with different feed ratios of xylan and fullerene derivatives.

[0044] Fig.15 FT-IR spectra of fullerene derivatives prepared under different conditions. DETAILED DESCRIPTION

[0045] The present invention is described in detail below with reference to the accompanying drawings. The raw materials mentioned in the present invention that are not described in detail are all commercially available products; the process steps or preparation methods that are not described in detail are all process steps or preparation methods well known to those skilled in the art.

[0046] Example 1 Preparation of xylan / fullerene derivative composite material

[0047] (1) Preparation of fullerene alcohol

[0048] Disperse 100 mg of fullerene in 50 mL of toluene, add 10 mL of 30% hydrogen peroxide solution and 500 μL of tetrabutylammonium hydroxide solution, and stir the reaction at 60 ° C and 400 rpm in a heated stirrer for 16 hours. After the reaction is completed, the lower layer of turbid liquid is obtained by decantation. Add 74 mL of isopropanol, 53 mL of anhydrous ether and 53 mL of n-hexane to the turbid liquid as precipitants. After a small amount of precipitate is produced, stir to dissolve the precipitate, transfer it to a centrifuge tube, and centrifuge it at 8000 rpm for 6 minutes to completely precipitate the fullerol and separate it from the toluene layer. After decantation to remove the supernatant, add an appropriate amount of anhydrous ether for washing, and repeat the above centrifugation-decantation steps 2 to 3 times to fully remove impurities. The obtained precipitate is placed in a vacuum oven for drying (vacuum degree: -1 MPa; temperature: 25 ° C), and the final yellow-brown solid product is fullerol.

[0049] The infrared spectrum of the prepared fullerenol was scanned, and the results were as follows: Figure 1 As shown. It can be seen that the product is at 3432cm -1 There is a vibration absorption peak of -OH (alcohol); at 1629cm -1 There is a stretching vibration peak of C=C at 1386cm -1 There is a bending vibration peak of COH at 1106cm -1 The presence of a bending vibration peak of CO at , verifies the successful synthesis of fullerene alcohol.

[0050] The prepared fullerenol was tested by nuclear magnetic resonance hydrogen spectrum, and the results were as follows Figure 2As shown, it can be seen that the peak at 2.60ppm is the characteristic peak of the solvent DMSO, and there is an obvious peak at 3.39ppm, which is the characteristic peak of -OH in fullerene alcohol.

[0051] Thermogravimetric analysis of the prepared fullerene alcohol showed the following results: Figure 3 As shown. It can be seen that the decomposition of fullerol is divided into three stages, among which the mass loss before 109.45℃ can be identified as the evaporation of free water in fullerol; the mass of fullerol decreased by 4.10% in the stage of 109.45℃~158.39℃, which may be because fullerol lost its crystal water as the temperature increased; 49.49% of the mass loss occurred at 158.39℃~432.45℃, which is related to the loss of hydroxyl groups in fullerol. When the temperature is higher than 432℃, the loss of mass may be attributed to the thermal loss of fullerene itself. According to the ratio of relative molecular mass is equal to the ratio of mass, the mass of the remaining fullerene carbon skeleton accounts for 40.96%, so the number of hydroxyl groups is set to n:

[0052]

[0053] From this, we can see that the number of hydroxyl groups on fullerol is about 51.

[0054] The above data all indicate that fullerenol was successfully prepared.

[0055] (2) Preparation of fullerene derivatives

[0056] Weigh 70 mg of betaine, 25 mg of EDC, and 15 mg of DMAP in 15 mL of deionized water, and stir at room temperature for activation for 1 hour. Then weigh 9.1 mg of fullerol and add it to the reaction system, and stir at room temperature for 24 hours. After the reaction is completed, the reaction solution is loaded into a dialysis membrane and dialyzed for 3 days, during which the dialysis water is replaced every 12 hours. After the dialysis is completed, the product in the dialysis membrane is taken out and centrifuged at 8000 rpm for 5 minutes. The supernatant obtained after centrifugation is freeze-dried, and the flocculent solid is finally obtained, which is the fullerene derivative.

[0057] The infrared spectrum of the prepared fullerene derivatives was scanned, and the results were as follows: Figure 4 As shown. It can be seen that the product is at 3440cm -1 There is a vibration absorption peak of -OH (alcohol); at 1633cm -1 There is a stretching vibration peak of C=C at 1382cm -1 There is a bending vibration peak of COH at 1084cm -1 There is a bending vibration peak of CO at 878cm -1 There is -N(CH 3 ) 3 The characteristic absorption peak of fullerene derivatives was confirmed.

[0058] The prepared fullerene derivatives were tested by nuclear magnetic resonance hydrogen spectrum, and the results were as follows Figure 5 As shown. It can be seen that the chemical shift of the characteristic peak of the solvent DMSO is at 2.60ppm; the peak signal at 3.40ppm is the strongest, which is the water peak produced by trace water; the signal at 1.24ppm is weaker, which is the characteristic peak of the hydroxyl group in fullerol that has not reacted with betaine; the signal at 3.81ppm is even weaker, which is the characteristic peak of the methyl group in the betaine molecule. Since there is no hydrogen atom on the ester group, it can only be judged by the characteristic peak of the raw material. The above analysis shows that the fullerene derivative was successfully synthesized.

[0059] The above data all indicate that fullerene derivatives were successfully prepared.

[0060] The yield of fullerene derivatives was 6.12%.

[0061] The yield of fullerene derivatives is calculated as:

[0062] (3) Preparation of xylan / fullerene derivatives

[0063] 3 mg of the fullerene derivative prepared in step (2) and 3 mg of xylan were dissolved in 3 mL of water, and the magnetic stirring speed was 600 r / min, and the reaction was stirred for 24 hours. The liquid after the reaction was dialyzed for 3 days, and the water was changed every 12 hours during the dialysis process. The supernatant obtained by centrifugation was freeze-dried to obtain a yellow-brown flocculent solid product, i.e., a xylan / fullerene derivative complex.

[0064] The preparation principle and structural formula of xylan / fullerene derivative composite materials are shown in the attached Figure 6 shown.

[0065] The infrared spectrum of the prepared xylan / fullerene derivative composite material was scanned. The results are as follows: Figure 7 As shown. It can be seen that the product is at 3427cm -1 There is a vibration absorption peak of -OH (alcohol); at 2922cm -1 There is a stretching vibration peak of CH at 1628cm -1 There is a stretching vibration peak of C=C at 1381cm -1 There is a bending vibration peak of COH at 1045cm -1 The presence of a bending vibration peak of CO at 147° verified the successful synthesis of the xylan / fullerene derivative complex.

[0066] The reaction raw materials (xylan, fullerol, betaine) and the prepared fullerene derivatives and xylan / fullerene derivative composite materials were tested by scanning electron microscopy. The results are as follows Figure 8 As shown, Figure 8 (a)-(e) are SEM images of fullerol, betaine, fullerene derivatives, xylan, and xylan / fullerene derivatives, respectively. It can be seen that xylan is in irregular flakes, betaine is severely agglomerated into one piece, while fullerol, fullerene derivatives, and xylan / fullerene derivatives are all irregular and have small particle sizes. In addition, fullerene derivatives have a better adsorption effect on xylan.

[0067] The prepared xylan / fullerene derivative complex was subjected to dynamic light scattering (DLS) particle size measurement, and the results were as follows: Fig. 9 As shown, the particle sizes of fullerol, fullerene derivatives, and xylan / fullerene derivatives are 304.0, 230.4, and 244.2 nm, respectively, and the particle sizes of the prepared particles are mostly between 114.5 and 520.9 nm.

[0068] The above data all indicate that the xylan / fullerene derivative complex was successfully prepared.

[0069] The mass ratio of xylan / fullerene derivative to fullerene derivative is 1.27.

[0070] The mass ratio of xylan / fullerene derivative to fullerene derivative is calculated as:

[0071] Example 2 Antioxidant properties of xylan / fullerene derivative composite materials

[0072] (1) NO free radical scavenging rate

[0073] ① Weigh a certain amount of xylan / fullerene derivative sample and dissolve it in deionized water, and prepare sample aqueous solutions with concentrations of (0.05 mg / mL, 0.1 mg / mL, 0.2 mg / mL, 0.4 mg / mL) in sequence.

[0074] ② Weigh a certain amount of sodium nitrosoferricyanide and dissolve it in phosphate buffered saline to prepare a 0.15 mg / mL sodium nitrosoferricyanide / phosphate buffered saline solution. Take 50 μL of this solution and 50 μL of each concentration gradient sample aqueous solution in columns 2-5 of a 96-well plate, and add 100 μL of deionized water in columns 1 and 6 as a blank control. Irradiate the 96-well plate under UVB light for 1 hour.

[0075] ③ Take out the irradiated 96-well plate and add 50 μL of Griess A solution containing 1% sulfonamide in phosphoric acid aqueous solution (phosphoric acid content is 2%) to all wells. Measure the absorbance of each well at 550 nm. The absorbance of the experimental group is recorded as A b The absorbance of the control group was recorded as A cb .

[0076] ④ Add 50 μL of Griess B solution containing 0.1% N-(1-naphthyl)ethylenediamine hydrochloride aqueous solution to each well in the experimental group and the aqueous solution in the first column, incubate at 25°C in the dark for 10 min, and measure the absorbance. The absorbance of the experimental group at this time is recorded as A s , the absorbance of the solution in each well in the first column is recorded as A c .

[0077] ⑤ Calculate by the formula: NO free radical inhibition rate % = [1-(A s -A b ) / (A c -A cb )] × 100. The inhibition rate of xylan / fullerene derivatives at different concentrations on NO free radicals was calculated. The average value was obtained by performing three parallel measurements. The specific results are shown in Table 1.

[0078] Fig.10 The NO free radical inhibition rate of the xylan / fullerene derivative composite material is measured. When the sample concentration is 0.05 mg / mL, the NO free radical inhibition rate is 62.7%; when the concentration is about 0.1 mg / mL, the NO free radical inhibition rate is 65.7%; when the concentration is about 0.2 mg / mL, the NO free radical inhibition rate is 73.8%; when the concentration is about 0.4 mg / mL, the NO free radical inhibition rate is 76.5%.

[0079] Table 1 NO free radical activity inhibition rate of xylan / fullerene derivative composites at different mass concentrations

[0080]

[0081] (2) Superoxide anion free radical scavenging rate

[0082] ① Weigh a certain amount of xylan / fullerene derivative sample and dissolve it in deionized water, and prepare sample aqueous solutions with concentrations of (0.05 mg / mL, 0.1 mg / mL, 0.2 mg / mL, 0.4 mg / mL) in sequence.

[0083] ② Weigh a certain amount of nitro blue tetrazolium chloride and dissolve it in deionized water to obtain a 0.274 mg / mL nitro blue tetrazolium chloride aqueous solution. Weigh a certain amount of reduced coenzyme I disodium and dissolve it in deionized water to obtain a 0.66 mg / mL solution. Weigh a certain amount of 5-methylphenazine methyl sulfate and dissolve it in deionized water to obtain a 0.018 mg / mL solution. Take 50 μL of each of the above three solutions and 50 μL of each concentration gradient sample aqueous solution in columns 2-5 of a 96-well plate, and then take 50 μL of each of the above three solutions and 50 μL of deionized water in column 1 of a 96-well plate as a blank control group. Columns 6-9 are used as background controls, and 50 μL of nitro blue tetrazolium chloride aqueous solution, reduced coenzyme I disodium, deionized water, and each concentration gradient sample aqueous solution are added.

[0084] ③ After 5 minutes of light-proof reaction, measure the absorbance of each well at 560nm. The absorbance of the experimental group is recorded as A, and the absorbance of the blank control group is recorded as A 1 The absorbance of the sample background control group is recorded as A 2 .

[0085] ④ Calculated by the formula: Superoxide anion free radical inhibition rate % = [1-(AA 2 ) / A 1 ]×100%. The inhibition rate of xylan / fullerene derivatives at different concentrations on superoxide anion free radicals was calculated. The average value was obtained by performing three parallel determinations. The specific results are shown in Table 2.

[0086] Fig.11 This is a graph showing the inhibition rate of superoxide anion radicals in xylan / fullerene derivative composite materials. When the sample concentration is 0.05 mg / mL, the inhibition rate of superoxide anion radicals is 14.6%; when the concentration is about 0.1 mg / mL, the inhibition rate of superoxide anion radicals is 22.7%; when the concentration is about 0.2 mg / mL, the inhibition rate of superoxide anion radicals is 42.1%; when the concentration is about 0.4 mg / mL, the inhibition rate of superoxide anion radicals is 46.7%.

[0087] Table 2 Inhibition rate of superoxide anion radical activity of xylan / fullerene derivative composites at different mass concentrations

[0088]

[0089] Example 3 Cytotoxicity test of xylan / fullerene derivative composite material

[0090] Dilute the cell suspension to a cell density of 1×10 5After 100 μL of the solution was added to each well, 5 wells were plated in each group, and the cells were placed at 37°C and 5% CO. 2 After the cells were well attached to the wall, the culture medium of each well was aspirated, and the experimental groups were added with basal culture medium containing 0.05 mg / mL, 0.1 mg / mL, 0.2 mg / mL, and 0.4 mg / mL of xylan / fullerene derivatives, and the blank group was added with basal culture medium without drugs. Then the 96-well plate was incubated at 37°C and 5% CO 2 Incubate in a cell culture incubator for 48 h. Prepare a CCK-8 solution containing 10% CCK-8 solution and add it to the culture medium as a replacement. Place the culture plate in a 37°C, 5% CO 2 After incubation in the incubator for 2 h, the OD value of each well at a wavelength of 450 nm was detected using an enzyme-labeled instrument. Fig.12 It can be seen that samples of various concentrations can promote cell proliferation, and the cells grow best when the dosage concentration is 0.2 mg / mL, indicating that the xylan / fullerene derivative composite material is non-toxic and can promote cell growth.

[0091] Example 4 Anti-inflammatory properties of xylan / fullerene derivative composite materials

[0092] After digestion, dilute with complete medium to a certain density (about 2×10 5 The intestinal epithelial cells (100 cells / dish) were plated into 6 small dishes and divided into a blank group, a control group, and an experimental group. They were cultured in a 37°C incubator for 24 hours until they were completely adhered to the wall, and the culture medium was aspirated. 5 mL of lipopolysaccharide (LPS) with a concentration of 2 μg / mL was prepared with basal culture medium, and 1 mL was transferred to each of the control group and experimental group small dishes to stimulate the adhered cells. After culturing in a 37°C incubator for 24 hours, the culture medium was aspirated. Different concentrations of xylan / fullerene derivative solutions (0.05, 0.1, 0.2, and 0.4 mg / mL) were prepared with basal culture medium, and 1 mL was transferred to each of the experimental group small dishes. 1 mL of basal culture medium was added to the blank group and control group small dishes, and they were cultured in a 37°C incubator for 24 hours. After loading the probe in situ, the fluorescence intensity was observed using a laser confocal microscope. For specific results, see Fig.13 : Fig.13 (a) is the blank group without stimulation and medication. Fig.13 (b) is the control group without drug administration after stimulation. Fig.13 (c)-(f) The fluorescence intensity of the control group was the strongest, while that of the experimental group gradually weakened with the increase of the concentration of xylan / fullerene derivatives. However, there was little difference between the 0.2 mg / mL and 0.4 mg / mL groups, and the fluorescence intensity was close to that of the control group.

[0093] Example 5 Effect of the Feed Ratio of Xylan and Fullerene Derivatives on the Mass Ratio of Xylan / Fullerene Derivatives to Fullerene Derivatives

[0094] Referring to Example 1, the mass ratio of xylan to fullerene derivative in step (3) was changed, and other conditions remained unchanged. The specific results of yield are shown in Table 3: When the mass ratio of xylan to fullerene derivative is 1:1, the mass ratio of xylan / fullerene derivative to fullerene derivative is the highest, which can reach 1.27, so this ratio is preferably used for preparation. The specific results of particle size are shown in Table 3. Fig.14 When the mass ratio of xylan to fullerene derivatives is 1:2, the particle size is much larger than that of other groups, indicating that the xylan / fullerene derivative complex is seriously agglomerated; when the mass ratio is 1:1, the particle size of the complex is slightly larger than that of the groups with mass ratios of 3:1, 2:1, and 1:3, indicating that the fullerene derivatives are more adsorbed on xylan and have stronger binding force.

[0095] Table 3 Effects of different xylan and fullerene derivative mass ratios on the mass ratio of xylan / fullerene derivatives and fullerene derivatives

[0096]

[0097]

[0098] Example 6 Effect of the feed ratio of betaine to fullerol on the yield of fullerene derivatives and the mass ratio of xylan / fullerene derivatives to fullerene derivatives

[0099] Referring to Example 1, the mass ratio of betaine to fullerol in step (2) was changed, and other conditions remained unchanged; the specific results of the yield of fullerene derivatives are shown in Table 4. The composite was prepared according to the steps of step (3) in Example 1, and the mass ratio of the obtained xylan / fullerene derivative and the fullerene derivative was shown in Table 4.

[0100] Table 4 Effects of different betaine to fullerol mass ratios on fullerene derivative yields, xylan / fullerene derivative to fullerene derivative mass ratios

[0101]

[0102] Comparative Example 1

[0103] The preparation of fullerene derivatives requires temperature control. Referring to Example 1, the temperature in step (2) is changed, while other conditions remain unchanged.

[0104] In addition, the temperature and other conditions in step (2) are controlled to remain unchanged, and a dilute HCl solution is added during the activation process at room temperature. The other reactions and treatments are carried out according to the scheme of Example 1.

[0105] The infrared spectra of the fullerene derivatives prepared under different conditions were scanned. Fig.15 As shown. It can be seen that the fullerene derivatives prepared under different conditions and the fullerene derivatives prepared under room temperature conditions have peaks at similar positions. Therefore, it is impossible to judge the rationality of each condition, and it is necessary to compare the yields. The specific yield results are shown in Table 5.

[0106] Table 5 Comparison of the yields of fullerene derivatives prepared under different conditions

[0107]

[0108] Therefore, the preparation reaction of fullerene derivatives was carried out at room temperature.

[0109] Comparative Example 2

[0110] The corresponding NO free radical scavenging rates of several antioxidant materials reported so far at a concentration of 0.4 mg / mL are shown in Table 6.

[0111] Table 6 Comparison of NO free radical scavenging rate between xylan / fullerene derivative composites and other materials

[0112]

[0113] [a]Hafsa J, Chaouch MA, Charfeddine B, et al. Effect of ultrasonicdegradation of hyaluronic acid extracted from rooster comb on antioxidant and antiglycation activities [J]. Pharmaceutical Biology, 2017, 55(1): 156-163.

[0114] [b]Velmurugan,N.,Kalpana,D.,Cho,JYet al.Chemical composition andantioxidant capacity of the aqueous extract ofPhellodendron amurense[J].Journal ofForestry Research,2018,29:1041-1048.

[0115] Compared with other materials in Table 6, the xylan / fullerene derivative composite material of the present invention has excellent antioxidant properties.

[0116] Comparative Example 3

[0117] The corresponding superoxide anion radical scavenging rates of several antioxidant materials reported so far at a concentration of 0.2 mg / mL are shown in Table 7.

[0118] Table 7 Comparison of superoxide anion radical scavenging rate of xylan / fullerene derivative composite materials and other materials

[0119]

[0120] [c] Cheng Jie, Chen Shuanglin. Study on the free radical scavenging ability of Acremonium fermentation broth extract [J]. Food Industry Science and Technology, 2010, 31(11): 155-157+423.

[0121] [d]Qing-an Zhang, Xi Wang, Yun Song, et al. Optimization of autooxidationconditions of catetriol and its application in evaluating the scavengingcapacity of superoxide anion radicals in four antioxidants[J]. FoodComposition andAdditives, 2016, 99(2):504-511.

[0122] Compared with other materials in Table 7, the xylan / fullerene derivative composite material of the present invention has excellent antioxidant properties.

[0123] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a xylan / fullerene derivative composite material, characterized in that: The method comprises: (1) betaine, DMAP, and EDC are mixed and stirred to activate, and then fullerene alcohol is added to react. After the reaction is completed, the mixture is dialyzed, centrifuged, and the supernatant is freeze-dried to obtain a fullerene derivative; (2) The obtained fullerene derivative and xylan are mixed in deionized water, stirred for reaction, dialyzed, and freeze-dried to obtain a xylan / fullerene derivative composite material.

2. The method according to claim 1, characterized in that In step (1), the mass ratio of fullerol to betaine is 1:(1-10).

3. The method according to claim 1, characterized in that In step (1), the mass ratio of DMAP to EDC is 3:(3-7).

4. The method according to claim 1, characterized in that: In step (1), the mass ratio of EDC to betaine is 1:(2-5).

5. The method according to claim 1, characterized in that In step (1), the activation temperature is 10-35°C; the activation time is 0.5-2h; the temperature of the mixed reaction is 10-90°C and the time is 12-36h.

6. The method according to claim 1, characterized in that In step (2), the mass ratio of the fullerene derivative to xylan is 1:3-3:

1.

7. The method according to claim 1, characterized in that In step (2), the dispersion concentration of the fullerene derivative in deionized water is 0.5-3 mg / mL.

8. The method according to any one of claims 1 to 7, characterized in that: In step (2), the stirring reaction temperature is 10-50°C and the time is 12-36h.

9. A xylan / fullerene derivative composite material prepared by the method according to any one of claims 1 to 8.

10. Use of the xylan / fullerene derivative composite material according to claim 9 in the preparation of antioxidant and anti-inflammatory preparations.